Bone marrow-derived dendritic cells pulsed with tumor lysates induce anti-tumor immunity against gastric cancer ex vivo - Li, Yan-Lin (The WJG Press and Baishideng, 2008)
AIM: To investigate whether bone marrow-derived dendritic cells pulsed with tumor lysates induce immunity against gastric cancer ex vivo. METHODS: c-kit(+) hematopoietic progenitor cells were magnetically isolated with a MiniMACS separator from BALB/c mice bone marrow cells. These cells were cultured with cytokines GM-CSF, IL-4, and TNFα to induce their maturation. They were analysed by morphological observation, phenotype analysis, and mixed lymphocyte reaction (MLR). Bone marrow-derived DCs (BM-DCs) were pulsed with tumor cell lysate obtained by rapid freezing and thawing at a 1:3 DC:tumor cell ratio. Finally, cytotoxic T lymphocyte (CTL) activity and interferon gamma (IFNγ) secretion was evaluated ex vivo. RESULTS: c-kit(+) hematopoietic progenitor cells from mice bone marrow cells cultured with cytokines for 8 d showed the character of typical mature DCs. Morphologically, observed by light microscope, these cells were large with oval or irregularly shaped nuclei and with many small dendrites. Phenotypically, FACS analysis showed that they expressed high levels of Ia, DEC-205, CD11b, CD80 and CD86 antigen, moderate levels of CD40, and negative for F4/80. Functionally, these cells gained the capacity to stimulate allogeneic T cells in MLR assay. However, immature DCs cultured with cytokines for 5 d did not have typical DCs phenotypic markers and could not stimulate allogeneic T cells. Ex vivo primed T cells with SGC-7901 tumor cell lysate-pulsed (TP) DCs were able to induce effective CTL activity against SGC-7901 tumor cells (E:T = 100:1, 69.55% ± 6.05% specific lysis), but not B16 tumor cells, and produced higher levels of IFNγ when stimulated with SGC-7901 tumor cells but not when stimulated with B16 tumor cells (1575.31 ± 60.25 pg/mL in SGC-7901 group vs 164.11 ± 18.52 pg/mL in B16 group, P < 0.01). CONCLUSION: BM-derived DCs pulsed with tumor lysates can induce anti-tumor immunity specific to gastric cancer ex vivo.